“la memoria campo minado”: Linguistic-temporal disruptions and queer becoming(s) in Sara Torres’ "Phantasmagoria" (2019) - Martín Díaz, Marta (Tropelías: Review of Literary Theory and Comparative Literature, 2023)
This article presents an analysis of the innovations and disruptions that the book Phantasmagoria (La Bella Varsovia, 2019), by writer Sara Torres, offers in the  Spanish contemporary poetic scene. To this end, on the one hand, the concept of 'phantasmagoria', the backbone of the book thanks to its inscription in a Sapphic genealogy (including Sappho herself and H.D.) and the theoretical substratum provided by new materialisms (through the work of authors such as Rosi Braidotti and Elizabeth Grosz) will be explored. On the other hand, attention will be paid to the disturbances and innovations in the use of language on both a poetic level and, mostly,  a typographic level throughout the collection. Finally, a brief analysis of the performance that, together with artists Marta Velasco Velasco and Ana Quiroga,  made the live presentation of this project will be presented. All these elements contribute to an understanding of memory in hermeneutic terms close to Muñoz's utopian proposal, and thus allow a queer becoming, beyond conventions, to  the enunciating body of the book.
Keywords: Sara Torres; Phantasmagoria; La Bella Varsovia; lesbian literature; queer poetics